2019
DOI: 10.1002/dvg.23324
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of DSPP‐Cerulean/DMP1‐Cherry reporter mice

Abstract: To gain a better understanding of the progression of progenitor cells in the odontoblast lineage, we have examined and characterized the expression of a series of GFP reporters during odontoblast differentiation. However, previously reported GFP reporters (pOBCol2.3-GFP, pOBCol3.6-GFP, and DMP1-GFP), similar to the endogenous proteins, are also expressed by bone-forming cells, which made it difficult to delineate the two cell types in various in vivo and in vitro studies. To overcome these difficulties we gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…A small fraction of the dividing cells showed activation of population-specific transcriptional biases, including an odontoblastic program. Obtaining cells of odontoblast sublineage became possible because we enriched for it by using Dspp cerulean /Dmp1 Cherry transgenic animals 38 . The immunohistochemistry confirmed activation of early odontoblast markers Notum and Sall1 in the near cervical loop mesenchymal area, indicating that odontoblast fate selection happens before embedding into the odontoblastic layer (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A small fraction of the dividing cells showed activation of population-specific transcriptional biases, including an odontoblastic program. Obtaining cells of odontoblast sublineage became possible because we enriched for it by using Dspp cerulean /Dmp1 Cherry transgenic animals 38 . The immunohistochemistry confirmed activation of early odontoblast markers Notum and Sall1 in the near cervical loop mesenchymal area, indicating that odontoblast fate selection happens before embedding into the odontoblastic layer (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Fos CreERT2 /R26 ZsGreen1 strain was used for genetic tracing of outer enamel epithelium progenitor cells. DMP1-Cherry/DSPP-cerulean mice were used for visualization of alveolar bone 38,49 . Acta2 CreERT2 /R26 tdTomato mice were used for lineage tracing of Acta2 + dental epithelial stem cells in cervical loop 31 .…”
Section: Methodsmentioning
confidence: 99%
“…All experimental protocols involving animal tissues in the present study were approved by the Institutional Animal Care and use Committee of UConn Health Center. DSPP-Cerulean/DMP1-Cherry, BSP-GFPtpz, pOBCol2.3FP (referred to as 2.3-GFP), TCF/Lef:H2B-EGFP, and nontransgenic mice used in this study have been previously described (Balic, Aguila, Caimano, et al 2010; Ferrer-Vaquer et al 2010; Vijaykumar et al 2019, 2020). All mice were maintained in the CD1 background.…”
Section: Methodsmentioning
confidence: 99%
“…pOBCol2.3-GFP (2.3-GFP) transgene is activated at early stages of odontoblast differentiation (preodontoblasts and prior to the expression of Dmp1 and Dspp ) (Balic, Aguila, and Mina 2010). DMP1-Cherry and DSPP-Cerulean transgenes are activated and expressed by functional and fully differentiated odontoblasts, respectively (Vijaykumar et al 2019). More recently, we showed that BSP-GFPtpz identifies cells in the osteogenic lineage and is excluded from cells in the dentinogenic lineage (Vijaykumar et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Odontoblasts synthesize and secrete dentin extracellular matrix proteins, among which DSPP and DMP1 are considered as typical marker for the odontogenic differentiation of mesenchyma stem cells [26] , and DMP1 might regulate the expression of DSPP [27] . Our results showed that the expression of NFIC, DSPP and KLF4 were inhibited and DMP1 was promoted by miR-143-3p.…”
Section: Discussionmentioning
confidence: 99%